2021
DOI: 10.1177/1540415320985581
|View full text |Cite
|
Sign up to set email alerts
|

Association of Accelerometer-Measured Physical Activity and Cardiovascular Health in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL)

Abstract: Introduction: Evidence regarding the associations between accelerometer-measured moderate-vigorous physical activity (MVPA) and cardiovascular health (CVH) indicators among Hispanic/Latino adults are unavailable. Methods: Examined cross-sectional data from 12,008 Hispanic/Latino adults aged 18–74 years participating in the Hispanic Community Health Study/Study of Latinos. Accelerometer-measured MVPA was assessed categorically and dichotomously per 2008 PA guidelines. Adverse and ideal CVH indicators were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Daily behaviors are inseparably bound to individuals’ cardiovascular health (CVH). As components of movement behaviors, the independent associations of sedentary behavior (SB), physical activity (PA), and sleep with CVH have been well established [ 1 4 ]. However, it is essential to recognize that SB, PA, and sleep collectively constitute a fixed 24-hour period, with each component interrelating and interacting with others, suggesting that changes in one component are likely to have a substantial effect on the associations between other components and health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Daily behaviors are inseparably bound to individuals’ cardiovascular health (CVH). As components of movement behaviors, the independent associations of sedentary behavior (SB), physical activity (PA), and sleep with CVH have been well established [ 1 4 ]. However, it is essential to recognize that SB, PA, and sleep collectively constitute a fixed 24-hour period, with each component interrelating and interacting with others, suggesting that changes in one component are likely to have a substantial effect on the associations between other components and health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review study with 29 studies reported that early sports practice with a higher weekly frequency, persistence for at least 3 years of practice, and the highest level of practice/competition were associated with higher levels of physical activity in adulthood [ 11 ]. In this sense, it is well established in the literature that higher physical activity levels are associated with better cardiovascular outcomes [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%